Exploring the Effects of Instagram and Firm Website on Corporate Performance: A Case Study of Cosmetics Firm - Tajdini, Javad; Tajeddini, Omid (Springer, 2023)
This essay aims to explore the effectiveness of the Instagram platform alongside a corporate’s website to promote multilevel marketing products. A combination of judgmental and convenience sampling methods was employed to determine how a small cosmetic online firm operates within the context of a protected, restricted, and ideological country like Iran. The findings indicate a possible connection between the social media platform, firm website, and corporate performance. The results show that utilizing a solid website and social media for multi-level marketing firms is essential but insufficient to enhance strong performance. Creating effective and efficient marketing campaigns is critical to improving social media’sinfluence. This study provides some practical insights for small online firms. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Corporate performance; Firm website; Instagram; Management perception; Social media